Character Education Socialization Pattern Among Young Generations in Perang Topat Tradition - M Zaki (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2021)
Character education is an action of educating the young generation to keep perfecting the individual self and practicing self competency toward the better life. This research aims to analyze the character education socialization pattern in young generation in perang topat (Topat War) tradition in Lingsar Village of Lombok Barat as the unit of analysis. This research employed qualitative method with case study approach, and then processed quantitative data collected from the result of field study through observation, in-depth interview, and documentation. The result of research shows that the character education socialization pattern in young generation in perang topat tradition in Lingsar Village of West Lombok consists of three patterns: socializing the symbolic meaning in perang topat tradition to the Young Generations, performing perang topat traditional practice annually, and preserving and then bequeathing this tradition to the Young Generations.